Biochemical Studies on Methylglyoxal-Mediated Glycated Histones: Implications for Presence of Serum Antibodies against the Glycated Histones in Patients with Type 1 Diabetes Mellitus. (7th August 2013) - Ansari, Nadeem A.; Dash, Debabrata
Abstract : Reactive carbonyl species (RCS) mainly reacts with lysine and arginine residues of proteins to form advanced glycation end products (AGEs). Histone was glycoxidated with glyoxal and methylglyoxal. It was characterized by polyacrylamide gel electrophoresis and quenching studies involving penicillamine and aminoguanidine as carbonyl scavengers. Further characterization of histone modified with methylglyoxal was done by UV, fluorescence, and IR spectrophotometry. Spectral analysis of the protein clearly demonstrates structural perturbation in the histone by methylglyoxal. Methylglyoxal-induces cross-linking in the protein leading to aggregation. Role of methylglyoxal mediated glycoxidation of histone in type 1 diabetes was also undertaken. Antibodies were detected against glycoxidated histone in sera of type 1 diabetes patients by solid-phase enzyme immunoassay. The findings indicate that as a result of structural perturbation in histone by methylglyoxal, the modified histone may be involved in production of serum antibodies in the diabetes patients.